Francophonie and the Orient French-Asian Transcultural Crossings (1840-1940) - Kang, Mathilde (Amsterdam University Press, 2018)
Based on transnational France-Asia approaches, this book studies Asian cultures once steeped in French civilisation but free of a colonial mode in order to highlight the transliterary examples of cultural transfer. This book is a pioneering study of the Francophone phenomenon within the context of cultures categorised as non-Francophone. Espousing a transcultural approach, Francophonie and the Orient examines the emergence of French heritage in the Far-East, the various forms of its manifestation, and the modes of its identification.Several thematic signposts guide the diverse pathways of the research. Firstly, the question is posed as to whether colonisation is the ultimate coat of arms for entry into Francophonie? Secondly, the book raises issues relative to Asian Francophone works: the emergence of literatures with French expression from Asian countries historically free of French domination. Finally, the study reconfigures the Asian Francophone heritage with new paradigms (transnational/global studies), which redefine the frontiers of Francophonie in Asia.